2011
DOI: 10.1186/1752-0509-5-71
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based simulation of reactions in the crowded and structured intracellular environment: Influence of mobility and location of the reactants

Abstract: BackgroundIn this paper we apply a novel agent-based simulation method in order to model intracellular reactions in detail. The simulations are performed within a virtual cytoskeleton enriched with further crowding elements, which allows the analysis of molecular crowding effects on intracellular diffusion and reaction rates. The cytoskeleton network leads to a reduction in the mobility of molecules. Molecules can also unspecifically bind to membranes or the cytoskeleton affecting (i) the fraction of unbound m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 55 publications
(99 reference statements)
0
87
1
Order By: Relevance
“…Other available tools (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) covered some but not all of these requirements. For this reason, the new PBRD package ReaDDy was developed (36).…”
Section: Introductionmentioning
confidence: 97%
“…Other available tools (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) covered some but not all of these requirements. For this reason, the new PBRD package ReaDDy was developed (36).…”
Section: Introductionmentioning
confidence: 97%
“…The vesicle model will be described below and it is embedded in an agent-based simulation method [61] extending the actions of those agents that represent vesicles or compartments.…”
Section: Methodsmentioning
confidence: 99%
“…found that the diffusion-lim ited reactions sense an interm ediate diffusion coefficient am ong the spectrum o f anom alous diffu sion coefficients [25]. G uigas et al show ed by sim ulations that anom alous subdiffusion increases the probability o f two nearby reactants encountering one another [26].…”
Section: Introductionmentioning
confidence: 97%